Alterations of Ultra Long-Chain Fatty Acids in Hereditary Skin Diseases—Review Article - Zwara, Agata; Wertheim-Tysarowska, Katarzyna; Mika, Adriana (Frontiers in Medicine, 2021)
The skin is a flexible organ that forms a barrier between the environment and the body's interior, involved in immune response, protection and regulation, and is a dynamic environment in which skin lipids play an important role in maintaining homeostasis. The different layers of skin differ in the composition and amount of lipids. The epidermis is best characterised in this respect. The main lipids in this layer are cholesterol, fatty acids and ceramides. Fatty acids can occur in free form and as components of complex molecules. The most poorly characterised fatty acids are very long chain fatty acids (VLCFA). VLCFA are among the main components of ceramides and are part of the free fatty acid fraction. They are most abundant in the brain, liver, kidneys and skin. VLCFAs are responsible for the rigidity and impermeability of membranes, forming the mechanically and chemically strong outer layer of cell membranes. Any change in the composition and length of the carbon chains of fatty acids (FAs) results in a change in their melting point and therefore a change in membrane permeability. One of the factors causing a decrease in the amount of VLCFA is an improper diet. Another and much more important factor are mutations in genes coding proteins involved in the metabolism of VLCFA - their elongation, attachment to ceramides and their transformation. These mutations have their clinical consequences in the form of, among others, inborn errors of metabolism and neurodegenerative disorders. Some of them are accompanied by skin symptoms such as ichthyosis, erythroderma or keratoderma. In the following review, the structure of the skin is briefly characterised and the most important lipid components of the skin are presented. The focus is also on providing an overview of selected proteins involved in the metabolism of VLCFA in the skin.